Juridical and colonial racisms: On Kant’s modern/colonial gender system - Jordan Pascoe (Rivista di Estetica)
This essay examines how inequalities are structured and rendered rightful in Kant’s political philosophy in order to offer a sketch of Kant’s juridical racism, or the ways in which his political philosophy is well-equipped to contain and maintain racial exclusions. By drawing on Nkiru Nzegwu’s conception of colonial racism, it highlights the forms of institutional racism that are perpetuated through juridical and colonial orders, which exceed Kant’s own theory of race, operating as what Huaping Lu-Adler has called a “racial ideology” embedded in his political philosophy. It first mines Kant’s arguments about the dependency of women in the Doctrine of Right, showing that these arguments offer a conceptual map of how raced inequality might be organized within the rightful state, organized as a form of juridical racism. It then turns to his cosmopolitan arguments, showing that working towards a rightful cosmopolitan condition will involve developing a shared conception of possessive rights, which Kant took to be a priori. In Kant’s inclusion of domestic right in this basic scheme of rightful possessive relations, we see an example of what Maria Lugones called the “modern/colonial gender system”, through which the invention and enforcement of normative gender roles becomes a critical method of coloniality. Thus, instead of treating gender as analogous to race in Kant’s arguments, I propose that we understand the normative structure of gendered dependency as a feature of Kant’s racial ideology.